2013
DOI: 10.1007/s00401-013-1135-4
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-dependent abnormalities in autophagy characterize human malformations of cortical development: evidence from focal cortical dysplasia and tuberous sclerosis

Abstract: Focal cortical dysplasia (FCD) is a localized malformation of cortical development and is the commonest cause of severe childhood epilepsy in surgical practice. Children with FCD are severely disabled by their epilepsy, presenting with frequent seizures early in life. The commonest form of FCD in children is characterized by the presence of an abnormal population of cells, known as balloon cells. Similar pathological changes are seen in the cortical malformations that characterize patients with tuberous sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 37 publications
2
53
0
Order By: Relevance
“…Moreover, similarly to FCD II, induction of apoptosis signaling pathways and premature activation of mechanisms of neurodegeneration, as well as a defect in autophagy [132], has also been observed in the tubers.…”
Section: Clinical and Neuropathologic Featuresmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, similarly to FCD II, induction of apoptosis signaling pathways and premature activation of mechanisms of neurodegeneration, as well as a defect in autophagy [132], has also been observed in the tubers.…”
Section: Clinical and Neuropathologic Featuresmentioning
confidence: 87%
“…Moreover, dysmorphic neurons and ballon/giant cells show nuclear and cytoplasmic accumulation of p62 [121], a stress-inducible intracellular protein, which is known to regulate different signal transduction pathways, and has been recently identified as a key target of autophagy (for reviews see [130,131]. A recent study confirms the mTOR-dependent abnormalities in autophagy, indicating a defect in autophagy as a common feature of FCD II and TSC [132]. The mTOR signaling (overactivated in both TSC and FCD II) is, indeed, a major negative regulator of autophagy ( [133]; for a review see [134]), and gene expression analysis of TSC cortical tubers revealed a deregulation of genes associated with ubiquitination [135].…”
Section: Pathogenesis and Molecular Geneticsmentioning
confidence: 92%
“…The mammalian target of rapamycin (mTOR) is a highly conserved serine/threonine protein kinase, and much evidence has accumulated indicating that the mTOR signaling pathway plays an important role in the pathogenesis of epilepsy (Meng et al, 2013;Yasin et al, 2013;Lee et al, 2014;Scheffer et al, 2014). TSC is an autosomal dominant hereditary disease denoted by epilepsy relating to aberrant activation of mTOR caused by TSC1/TSC2 gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…A few balloon cells in FCDIIB cases showed some fine granular PAS-positive staining in the cytoplasm (Fig 2C) or sometimes at the margins of the cell (Fig 2C, inset), reminiscent of the patterns reported in the cell culture of balloon cells, with accumulation of dense core lysosomes. 22 Balloon cells in FCDIIB cases also showed p62 immunopositivity, displaying both Four of these proteins (clathrin, dynamin, syntaxin binding protein, and vesicle-associated membrane protein 2) had been described in a previous study investigating the proteome of lipofuscin in aged and Alzheimer'sdiseased human brains (Ottis et al, 2012). At the presynaptic terminal of neurones, synaptic vesicles are actively loaded with neurotransmitters (NT) and then they are docked and "primed" at the "active zone" of the plasma membrane.…”
Section: Liu Et Al: Frontal Lobe Epilepsy With Lipofuscinmentioning
confidence: 99%